MENTAL EMOTIONAL CHANGES WITH EATING DISORDERS IN ADOLESCENTS AGED 13-17 YEARS - Iva Milia Hani Rahmawati; Inayatur Rosyidah; Zulvana; Anin Wijayanti (Nursing Sciences Journal, 2025)
Eating disorders are eating disorders that are often experienced by adolescents. Most adolescents consume unhealthy foods causing disturbed eating patterns. Adolescence is a transition period from childhood to adulthood, the transition includes many aspects, one of which is emotional mentality, which triggers deviant eating behavior known as eating disorders. This study aims to analyze the relationship between emotional mental changes and eating disorders in adolescents aged 13-17 years in Tegalsari Village, Tulungrejo, Pare-Kediri. This type of research is quantitative with a cross-sectional approach design. The population of adolescents with emotional mentality and eating disorders was taken by simple random sampling, a sample of 45 respondents was obtained. The independent variable in this study is emotional mentality which is measured using a questionnaire and the dependent variable in this study is eating disorders which are measured using a questionnaire with data processing using the Spearman rank test analysis. The results showed that of the 45 respondents, most of them experienced bad emotional mentality. and most of them had eating disorders with bad categories. based on the Spearman rank test, the p value = 0.012 was obtained, so H1 was accepted. The conclusion is that there is a close relationship between emotional mental changes and eating disorders in adolescents aged 13-17 years. Suggestion It is hoped that teenagers can maintain good mental health and eating patterns so that they can grow and develop according to their age.